Critical decision-making in radiotherapy for early stage breast cancer in a neo-adjuvant treatment era. Issue 5 (4th May 2017) - De Felice, Francesca; Osti, Mattia Falchetto; De Sanctis, Vitaliana; Musio, Daniela; Tombolini, Vincenzo
ABSTRACT: Introduction: In breast cancer management, the role of adjuvant radiation therapy (RT) has been the subject of intense controversy over the past several years, due to the improvement in neoadjuvant chemotherapy (NACT) prescription. One of the most controversial questions regarding indication for adjuvant RT is whether or not RT is essential in patients with early stage disease at diagnosis. The value of adjuvant RT remains highly debatable in those patients with clinically negative nodes at the completion of NACT. Areas covered: This review is focused on this gray area and is intended to assist with clinical decision-making. We provide a comprehensive review using PubMed and meeting proceedings of San Antonio Breast Cancer Symposium, European Society for Radiotherapy & Oncology, European Society of Medical Oncology and American Society of Clinical Oncology. Expert commentary: The identification of potential prognostic factors may lead to novel adjuvant RT indications. Phase III clinical trials are underway and their results will help guide treatment decisions.